Analysis and countermeasure to improve machine efficiency by using overall equipment effectiveness (OEE) method - Law, Jessica Ka Ing (2015)
To compete in global market, no organization will tolerate losses Overall Equipment Effectiveness (OEE) is a novel technique to measure the effectiveness of a machine and it truly reduces complex production problems into simple and intuitive presentation of information. It considers all important measures of productivity. An attempt has been done to measure and analyze existing Overall Equipment Effectiveness (OEE) at JSC Paper Mill Sdn. Bhd. in hope to reduce unplanned downtime losses on equipment failure and tooling damage to maximize the productivity. Before obtaining the data to calculate the existing OEE value, the product or process that have the highest downtime rate need to be identified which is Toilet Tissue converting process at Converting Department. The methods used to analyze these various causes were Ishikawa diagram, Pareto Analysis, 5 Whys and 5W1H. After knowing the causes of various activities that leads to high downtime rate, then recommendations for improvements that could be used by JSC Paper Mill were ready to be made.